1986
DOI: 10.1080/00288233.1986.10426968
|View full text |Cite
|
Sign up to set email alerts
|

Response to phosphorus of populations of white clover

Abstract: The response to phosphorus (P) of 8 semi-natural populations and 2 cultivars of white clover was investigated in 3 experiments. Vegetatively propagated plants from 15 genotypes of each population were planted into mixed swards, both grazed and cut, and into pure clover swards. These swards received various amounts of fertiliser P. In all 3 experiments, populations collected from low P soils had a higher percentage survival and higher yields than populations collected from high P soils. However, in all 3 experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 15 publications
3
24
0
Order By: Relevance
“…Selection for high P-response and low P-response populations of white clover in a controlled environment was not effective in producing lasting differences in growth of white clover in a low-P soil environment fertilised to a range of P fertility levels. Other studies have shown a similar disparity between controlled environment and field trials for growth response of white clover to P (Caradus & Snaydon 1986. In the glasshouse, selections were made principally on the basis of response to P, whereas in the present work low P was only one of a number of stresses encountered.…”
Section: Discussionmentioning
confidence: 67%
“…Selection for high P-response and low P-response populations of white clover in a controlled environment was not effective in producing lasting differences in growth of white clover in a low-P soil environment fertilised to a range of P fertility levels. Other studies have shown a similar disparity between controlled environment and field trials for growth response of white clover to P (Caradus & Snaydon 1986. In the glasshouse, selections were made principally on the basis of response to P, whereas in the present work low P was only one of a number of stresses encountered.…”
Section: Discussionmentioning
confidence: 67%
“…However, significant population x P interactions might have been expected, since the populations have been shown to differ in response to phosphorus (Davies and Snaydon, 1974). The absence of such interactions may partly reflect the relatively small effects of phosphorus on the performance of spacedplants in this study (table 6), but may also be the result of the absence of competition, as shown by Caradus and Snaydon (1986).…”
Section: Environmental Conditionsmentioning
confidence: 68%
“…Numerous studies by plant breeders, using both forage species (e.g., Lazenby, 1957;Knight, 1960;Copeman and Swift, 1966) and crop species (e.g., Syme., 1972;Fischer and Kertez, 1976), have shown that only weak correlations exist between the yield of genotypes or populations as spaced-plants and their yield in dense monocultures. Few such comparisons have been made in the context of the ecological genetics of plant species, and the effects of competition on attributes other than yield have received little attention, though Caradus and Snaydon (1986) have compared populations of T repens for a number of morphological and physiological attributes in a diversity of conditions; they found widely different correlations, depending on the particular attributes and conditions considered.…”
Section: The Spaced-plant Trial Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…This method also better predictor of similarities or dissimilarities (Marilley 1999;Hebeisen 1997;Deiglmayr 2006;Caradus 1986;Caradus 1992). Table 3 show that describing more than 70%, cumulative percent plant characteristics should be examined in five groups (Eigen value: 1,1254, proportion:0,080,cumulative percent: 76,1%).…”
Section: Flowermentioning
confidence: 99%